The hidden gem: exploring the allure of Kedah / Noorliza Zainol … [et al.] - Zainol, Noorliza; Razali, Mohamad Azli; Din, Norrina; Abdul Hadi, Arnieyantie (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
Introduction Nestled in the northwestern region of Peninsular Malaysia, Kedah might not always be the first destination that comes to mind when one thinks of Malaysia's tourist hotspots. However, this charming state, often overshadowed by its more illustrious neighbours, is a hidden gem teeming with cultural richness, culinary delights, and natural beauty. Kedah, known as the "Rice Bowl" of Malaysia, offers an array of experiences that weave together its unique historical legacy, delectable food, and picturesque landscapes. This article delves into the multifaceted allure of Kedah, offering insights into its culture, gastronomy, and geographical features, as well as recommendations for those seeking an off-the-beaten-path adventure.